Russian registry of Infliximab.Impact of therapy on the functional status of patients with rheumatoid arthritis - V N Amirdzhanova; Elena Yur'evna Kaygorodtseva; D V Goryachev; G V Lukina; E S Pozdnyakova; Ya A Sigidin; E L Nasonov; V N Amirdzhanova; Elena Yuryevna Kaigorodtseva; D V Goryachev; G V Lukina; E S Pozdnyakova; et al. (Научно-практическая ревматология, 2010)
Objective. To evaluate the functional state of rheumatoid arthritis (RA) patients receiving Infliximab therapy (IF) in real clinical practice and its efficiency. Subjects and methods. The analysis covered 225 patients receiving IF therapy, the follow-up duration in whom was 54 weeks. Disease activity was estimated by the DAS 28 index; functional status was assessed according to the Health Assessment Questionnaire (HAQ). The authors made an analysis of a Per-Protocol (PP) population (n = 154) at 54 weeks of treatment and an analysis that could consider the results of treatment (by the ACR and EULAR criteria) in patients who had been withdrawn before the control time - a LOCF (Last Observation Carried Forward analysis) population. Results. The mean age of the patients was 47.6±11.4 years; the duration of the disease was 7.8±6.4 years; DAS 28 activity scores were 6.6±1.1; the majority of patients had significant functional impairments (HAQ scores of 2.0±0.7), 86.7% of the patients had extraarticular manifestations; 79.6% were found to have rheumatoid factor (RF); the patients received an average of > 2 disease-modifying antirheumatic drugs (DMARDs). After 2 week-therapy, there was a reduction in RA activity by DAS 28 index in both the PP (from 6.7±1.1 to 4.0±1.4) and LOCF (6.6±1.1 and 4.2±1.4; p < 106) populations. Drug-induced remission (DAS 28 < 2.6) at 54 weeks was observed in 16.9 and 15.1% of the patients, respectively. Functional improvement was noted in the PP population: HAQ decreased from 2.0±0.7 to 1.7±0.7 scores by week 2; its reduction continued until week 14 (p < 0.05), by remaining stable later on. HAQ dropped from 2.0±0.7 to 1.2±0.7 scores in the LOCF population. At 54 weeks, normal population values of functional activity were achieved in 16.4%. Log regression analysis in the LOCF population indicated that the previous use of DMARDs and a short history of the disease were predictors of an ACR70 response to IF therapy [OR=1.61 (1.13-2.30), p = 0.008 and OR = 0.91 (0.84-0.98), p = 0.018, respectively]. RF seronegativity was a predictor for achievement of low RA activity [OR = 0.44 (0.23-0.84)]. The previous use of glucocorticoids failed to increase the probability of a good response to IF therapy and achievement of clinical remission [OR = 0.26 (0.11-0.60), p = 0.001]. Conclusion. Therapy with IF in combination with methotrexate or other DMARDs reduces RA activity and improves the functional capacities of patients with RA in real clinical practice.